Enhancing Learning Outcomes, Motivation, and Self-Efficacy in Sociodrama through a Blended Spinner Application and Role-Playing Method - Rafik Abasa; Roni Kurniawan; Iwan Abdy; Andi Rahmadani; Pamuti Pamuti; Lis Susilawati (Jurnal Ilmiah Global Education, 2026)
This study addresses the challenge of low student engagement and performance in sociodrama within secondary education. Conventional teaching methods often lead to passive learning, lack of confidence, and inadequate understanding of role-playing techniques. The aim of this research is to investigate the effectiveness of a blended pedagogical approach combining a digital Spinner Application and Sociodrama (Role-Playing) to enhance learning outcomes, motivation, and self-efficacy among students. The research employed a Classroom Action Research (CAR) design, conducted over two cycles with 30 Grade XI Social Studies students at MAN 1 Ternate City, Indonesia. Methods included direct observation, performance rubrics, and pre- and post-intervention questionnaires measuring motivation and self-efficacy using a 5-point Likert scale. The results showed significant improvements: average spontaneity scores rose from 83.33 (Cycle I) to 88.67 (Cycle II), and structured performance scores increased from 82 (pre-test) to an average of 89.5 (Cycle II). Motivation increased by 63.4% and self-efficacy by 76.8%. The blended method successfully reduced anxiety, increased participation, and improved both cognitive and affective learning domains. These findings support the integration of gamification and experiential learning in drama education.